Distrusted disclosures: Deception drives anti-transgender but not anti-atheist prejudice - Totton, Rebecca R.; Rios, Kimberly; Shogren, Nathaniel (Frontiers in Psychology, 2023)
Introduction Transgender individuals face high levels of prejudice in interpersonal relationships. However, limited experimental research has examined the role of identity disclosure on anti-transgender prejudice. Methods Drawing upon research on distrust and identity disclosure, two between-participants experiments (total n = 802) examined the role of intentional and unintentional identity disclosure on negative attitudes (Studies 1 & 2), perceived deception (Studies 1 & 2) and distrust (Study 2) toward two potentially concealable and historically distrusted identities (transgender and atheist). Specifically, the current studies examine the impact of a target’s stigmatized identity (transgender or atheist) and method of disclosure (intentional or unintentional) on perceptions of the target, perceived deceptiveness, and distrust toward the target. Results Our findings demonstrated that compared to atheists, transgender targets elicited greater levels of prejudice and were viewed as more deceptive, and that this effect was amplified if the target did not intentionally reveal their identity. Study 2 demonstrated that perceived deception mediated the relationship between reveal type (i.e., intentional vs. unintentional) and prejudice toward participants who read about a transgender (but not atheist) target. Discussion We discuss the implications of these findings for reducing prejudice toward binary transgender individuals, particularly those who do not voluntarily disclose their identity.